2022
DOI: 10.20853/36-6-5525
|View full text |Cite
|
Sign up to set email alerts
|

Belonging, wellbeing and stress with online learning during COVID-19

Abstract: Sense of belonging, perceived stress and wellbeing are reported factors that influence students’ university experience and learning. The COVID-19 pandemic and shift to online emergency remote teaching were likely to exacerbate these affective dimensions of student experience. This article employed a quantitative survey research design to determine how students’ sense of belonging, perceived stress and wellbeing were influenced during the pandemic. An online questionnaire was administered to 537 South African s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…This study found that 25% of the study participants had symptoms of perceived stress, which is comparable to the rate of 29.5% [12], however, lower than the rate of 78% [9], 87% [11], and the rate ranging from 61.8% to 71.2% [13] reported in SA studies conducted before the pandemic. The lower rate in our study could be due to the psychosocial support services introduced for students during and after the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…This study found that 25% of the study participants had symptoms of perceived stress, which is comparable to the rate of 29.5% [12], however, lower than the rate of 78% [9], 87% [11], and the rate ranging from 61.8% to 71.2% [13] reported in SA studies conducted before the pandemic. The lower rate in our study could be due to the psychosocial support services introduced for students during and after the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 55%
“…The lower rate in our study could be due to the psychosocial support services introduced for students during and after the COVID-19 pandemic. Another possible reason could be that some studies used the General Health Questionnaire -28 (GHQ-28) [13] and Depression, Anxiety, and Stress Scale (DASS-21) [12] Variables n (%) to measure perceived stress, while our study used the PSS-10 tool. We further analysed individual PSS items and found that the items that achieved the highest and the lowest PSS scores were "In the last month, how often have you felt nervous and stressed?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a sense of belonging is a key component for all students in educational inclusion and wellbeing (Theron and Liebenberg, 2015;Blignaut et al, 2022), the development of this feeling is a challenging journey for newly arrived migrant pupils. In particular, issues of linguistic and cultural misrepresentation, unequal learning opportunities and outcomes, stereotyping, discrimination and racism still occur in schools (Council of Europe, 2017;UNESCO, 2018;Szelei et al, 2019Szelei et al, , 2021a.…”
Section: Introductionmentioning
confidence: 99%
“…The shift to fully online settings from face-to-face and blended forms of instruction, learning, and assessment changed the educational landscape. Different approaches to pedagogy design, delivery, and evaluation continue to be crucial to what could or should be consistent to the academics' competencies (Blignaut et al 2022). The majority of basic education and higher education systems were exposed to the new online form of education for the first time, while some who had prior exposure to this sector were presented with fully fledged online tests and lectures for the first time (Pandit and Agrawal 2022).…”
Section: Introductionmentioning
confidence: 99%